Effect of anaemia on the response to preoperative chemoradiotherapy for rectal cancer. Issue 5 (6th January 2021) - Bong, Jun Woo; Lim, Seok‐Byung; Ryu, Hyoseon; Lee, Jong Lyul; Kim, Chan Wook; Yoon, Yong Sik; Park, In Ja; Yu, Chang Sik; Kim, Jin Cheon
Abstract: Backgrounds: Radiation therapy with concurrent chemotherapy is an important treatment for rectal cancer, especially for advanced stage disease. Low serum haemoglobin levels are accepted as a negative indicator in the response to radiation therapy. This study aimed to evaluate the relationship between anaemia and the response to preoperative chemoradiotherapy for rectal cancer and its effect on oncologic outcomes. Methods: We retrospectively reviewed medical records of primary rectal cancer patients who were treated with preoperative chemoradiotherapy followed by total mesorectal excision between January 2011 and December 2015. Anaemia was defined as serum haemoglobin levels ≤9 g/dL before or during radiotherapy. Patients were divided into good and poor responders according to pathologic tumour regression grades. The effect of anaemia on the response to radiation therapy, recurrence‐free survival and overall survival were analysed after subgroup analysis. Results: Overall, 301 and 394 patients were categorized into good and poor responder groups, respectively. Proportions of anaemia patients were higher in the poor responder group than in the good responder group (7.6% versus 4.0%, P = 0.042). Anaemia was associated with less pathologic complete regression but was not a risk factor for worse recurrence‐free or overall survival. There was no significant difference in survival between patients with and without anaemia. Conclusion: Haemoglobin levels ≤9 g/dL before or during radiotherapy were risk factors for achieving pathologic complete regression after preoperative chemoradiotherapy for rectal cancer. However, anaemia was not independently associated with worse survival outcomes. Abstract : Haemoglobin levels ≤9 g/dL before or during radiotherapy were risk factors for achieving pathologic complete regression after preoperative chemoradiotherapy for rectal cancer. However, anaemia was not independently associated with worse survival outcomes.